The Effect Of Service Quality and Consumer Knowledge On Purchase Decisions Through Trust, With Price and Location as Moderating Variables In Pharmacies - Yeni Mardiyani; Nizar Alam Hamdani; Oktri M Firdaus (Jurnal Inovasi Bisnis dan Kewirausahaan, 2026)
The pharmaceutical retail sector in Garut faces intense competition, where purchasing decisions are heavily influenced by perceived risk and trust. This study aims to analyze the effect of service quality and consumer knowledge on purchasing decisions through trust as a mediating variable, while examining price and location as moderating variables. Using a descriptive and verificative quantitative approach, data were collected from 275 respondents via semantic differential scale questionnaires (1-7) and analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with SmartPLS 4.0. The results show that service quality and consumer knowledge significantly affect trust. Trust is the dominant variable influencing purchasing decisions with a path coefficient of 0.184. Information honesty and staff responsiveness are key factors in building consumer confidence. Moderation tests prove that price and location significantly strengthen the impact of service quality on purchasing decisions. An R-Square value of 0.824 indicates the model explains 82.4% of the purchasing decision. Descriptive findings reveal that despite high selection stability, long-term loyalty requires strategic reinforcement. In conclusion, trust is the primary determinant of purchasing decisions. Management strategies should prioritize product transparency and pharmaceutical education to transform situational purchasing behavior into sustainable loyalty by optimizing location accessibility and price rationality.